Γ-Tocotrienol induced the proliferation and differentiation of MC3T3-E1 cells through the stimulation of the Wnt/β-catenin signaling pathway. Issue 1 (15th December 2021) - Xu, Weili; Li, Yutong; Feng, Rennan; He, Pan; Zhang, Yuqi
Abstract : The mechanism of γ-T3-induced proliferation and differentiation of MC3T3-E1 cells via the activation of the Wnt/β-catenin signaling pathway by allowing the stabilization and nuclear translocation of β-catenin. Abstract : γ-Tocotrienol (γ-T3), an isoprenoid phytochemical, has shown the promotion of osteoblast proliferation and differentiation in our previous study. In this study, its underlying mechanism was investigated through regulating the Wnt/β-catenin signaling pathway in MC3T3-E1 cells. Comparative experiment results showed that γ-T3, not α-tocopherol (α-TOC) increased more significantly the viability and differentiation in MC3T3-E1 cells. After that, the cells were incubated with 10 mM LiCl, or 4 μM γ-T3 with or without 1 μM XAV-939. γ-T3 at 4 μM stimulated the Wnt/β-catenin signaling pathway by increasing the expression and nuclear accumulation of β-catenin, and the expressions of their downstream factors, such as cyclin-D1, c-Myc, BMP2 and BMP-4 in MC3T3-E1 cells. γ-T3 not only upregulated the viability, induced G0/G1 to the S phase, and promoted the expressions of PCNA (Proliferating Cell Nuclear Antigen) and Ki-67, but also increased ALP activity and the expressions of ON, OPN and OCN. Moreover, the effects of γ-T3 on the MC3T3-E1 cells resembled the actions of LiCl, an activator of the Wnt/β-catenin signaling pathway. Notably, all these effects of γ-T3 on the MC3T3-E1 cells were completely blocked by the Wnt/β-catenin signaling pathway inhibitor XAV-939. Our data demonstrated that γ-T3 can target β-catenin to enhance the Wnt/β-catenin signaling pathway, which led to increased expressions of the downstream cell proliferation and cell cycle-associated (cyclin D1 and c-myc), and cell differentiation-associated (BMP-2 and BMP-4) target genes, and ultimately promoted MC3T3-E1 cell proliferation and differentiation. Therefore, γ-T3 may be a potential agent to prevent and reverse osteoporosis due to its safety and powerful abilities of osteogenesis.